IMPLIKASI DAN SOSIALISASI UNDANG-UNDANG TENTANG PERLINDUNGAN DATA PRIBADI DALAM MENJAGA KERAHASIAAN DATA PRIBADI SESEORANG - Krista Yitawati; Sarjiyati; Yuni Purwati; Bambang Sukarjono (Universitas Merdeka Madiun, 2022)
This journal aims to carry out the tridharma obligation, namely community service where we provide education about the implications and socialization of the Personal Data Protection Act in maintaining the confidentiality of one's personal data. The method used is to conduct a survey to the target community and conduct socialization and education directly to the community. The Personal Data Protection Law is a manifestation of the state's protection for the fulfillment of the privacy rights of its citizens, but there are still many challenges from the implications that the government and society must go through with this regulation, especially in interpreting the various interests regulated in the law. personal data protection regulations that are still very general, ensure proper implementation and supervision, as well as synchronization with various other laws and regulations. For this reason, more intense socialization is needed and has a broad impact on the community, business actors, students, etc. so that the regulation on the protection of personal data can be carried out properly and can be beneficial for various parties.